2017
DOI: 10.1097/pcc.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload and Kidney Injury Score: A Multidimensional Real-Time Assessment of Renal Disease Burden in the Critically Ill Patient*

Abstract: A multidimensional score of renal disease burden was significantly associated with adverse PICU outcomes. Further studies will evaluate Fluid Overload Kidney Injury Score as a warning and decision support tool to impact patient-centered outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The FOKIS study by Akcan-Arikan et al (14) demonstrated that higher FOKIS was associated with morbidity and mortality in PICU. Our study is the first in pediatrics to use a decision-support tool for identifying patients at risk of VAC and/or IVAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The FOKIS study by Akcan-Arikan et al (14) demonstrated that higher FOKIS was associated with morbidity and mortality in PICU. Our study is the first in pediatrics to use a decision-support tool for identifying patients at risk of VAC and/or IVAC.…”
Section: Discussionmentioning
confidence: 99%
“…The FOKIS comprises three variables; (1) AKI severity according to pRIFLE, (2) FO severity, and (3) nephrotoxic medication exposure (Supplementary Material Table 1). This scoring system serves as a decision support tool for identification of patients with renal disease burde (14) at our institution.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All subjects were normalized to 0% FO after RAI calculation and FO was calculated thereafter. Cumulative FO was then calculated every 12 h through 96 h according to previously published definitions [ 14 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Despite this, evidence suggests that in daily practice, clinicians fail to recognize nearly one-third of patients who have significant FO and patients continue to receive unrecognized levels of fluid administration [ 19 , 22 , 23 ]. This delayed recognition likely contributes to worse outcomes [ 14 , 19 ]. Currently, there are no instruments to assist clinicians’ identification of patients at risk for the development of significant FO.…”
Section: Introductionmentioning
confidence: 99%